Isolation of the thymidylate synthetase gene (TMP1) by complementation in Saccharomyces cerevisiae. - Taylor, G R (1982)
The structural gene (TMP1) for yeast thymidylate synthetase (thymidylate synthase; EC 2.1.1.45) was isolated from a chimeric plasmid bank by genetic complementation in Saccharomyces cerevisiae. Retransformation of the dTMP auxotroph GY712 and a temperature-sensitive mutant (cdc21) with purified plasmid (pTL1) yielded Tmp+ transformants at high frequency. In addition, the plasmid was tested for the ability to complement a bacterial thyA mutant that lacks functional thymidylate synthetase. Although it was not possible to select Thy+ transformants directly, it was found that all pTL1 transformants were phenotypically Thy+ after several generations of growth in nonselective conditions. Thus, yeast thymidylate synthetase is biologically active in Escherichia coli. Thymidylate synthetase was assayed in yeast cell lysates by high-pressure liquid chromatography to monitor the conversion of [6-3H]dUMP to [6-3H]dTMP. In protein extracts from the thymidylate auxotroph (tmp1-6) enzymatic conversion of dUMP to dTMP was barely detectable. Lysates of pTL1 transformants of this strain, however, had thymidylate synthetase activity that was comparable to that of the wild-type strain.